Enhanced activation of peroxymonosulfte by LaFeO3 perovskite supported on Al2O3 for degradation of organic pollutants. (December 2019) - Wu, Shaohua; Lin, Yan; Yang, Chunping; Du, Cheng; Teng, Qing; Ma, Yin; Zhang, Dongmei; Nie, Lijun; Zhong, Yuanyuan
Abstract: In this study, the effect of various supports on activation of peroxymonosulfate and consequent degradation of Acid Orange 7 (AO7) in aqueous solutions was examined at the presence of LaFeO3 perovskite as catalyst. Results showed that the AO7 degradation efficiency by LaFeO3 supported on different supports was in an order of LaFeO3 /Al2 O3 (86.2%) > LaFeO3 (70.8%) > LaFeO3 /CeO2 (59.0%) > LaFeO3 /SiO2 (52.3%) > LaFeO3 /TiO2 (32.2%). Moreover, the pseudo first-order rate constant for AO7 degradation by LaFeO3 /Al2 O3 was 3.2 times than that by LaFeO3 . The enhancement was attributed to its large surface area, abundant chemisorbed surface-active oxygen, redox property and faster electron transfer. AO7 degradation and the leaching of iron ions decreased with the increase of pH. Data of electron spin resonance spectroscopy and quenching experiments revealed that sulfate and hydroxyl radicals were generated on LaFeO3 /Al2 O3 surface, while sulfate radicals were identified to be the main reactive species responsible for AO7 degradation. Mechanisms for peroxymonosulfate activation were consequently proposed. Furthermore, LaFeO3 /Al2 O3 catalyst exhibited a superior stability after five cycles. This work provides a new approach for design of iron-based perovskite catalysts with high and stable catalytic activity for removal of organic pollutants from aqueous solutions. Graphical abstract: Image 1 Highlights: Catalysts of LaFeO3 perovskites were successfully prepared by the citric sol-gel method. Support effect on catalytic properties of LaFeO3 for PMS activation was reported. LaFeO3 /Al2 O3 showed the highest activity for AO7 degradation than other supported catalysts. Surface-bound sulfate radical was identified responsible for AO7 degradation.